Arsenite removal from groundwater by iron–manganese oxides filter media: Behavior and mechanism. (21st February 2019) - Cheng, Ya; Zhang, Shasha; Huang, Tinglin; Li, Ye
Abstract: Arsenic, a common contaminant in groundwater environments, usually coexists with other contaminants, for example, ammonium, iron, and manganese. In our previous studies, an iron–manganese (Fe–Mn) oxides filter media was developed for catalytic oxidation removal of ammonium, iron, and manganese. In this study, batch oxidation/adsorption kinetic experiments revealed that the filter media could easily oxidize arsenite (As(III)) to arsenate (As(V)). And the sorption kinetics was found to follow the pseudo‐second‐order kinetic model. X‐ray powder diffraction (XRD) and Fourier transform infrared spectra (FTIR) along with X‐ray photoelectron spectroscopy (XPS) were used to analyze the surface change in the Fe–Mn oxides. Based on sorption and spectroscopic measurements, the mechanism of As(III) removal by the Fe–Mn oxides filter media was found to be an oxidation coupled with sorption approach. As(III) in the aqueous solution was firstly oxidized to As(V) on the surfaces of the Fe–Mn oxides filter media. Then the converted As(V) was attracted to the Fe–Mn oxides filter media surfaces and bounded with the active sites (−OH groups), through weak intermolecular H‐bondings. Our results indicated that the novel Fe–Mn oxides filter media could be applied for the simultaneous removal of ammonium, iron, manganese, and As(III) in drinking water treatment and environmental remediation. Practitioner points: A novel iron–manganese oxides filter for efficient As(III) removal was established. The exhausted filter media could be easily regenerated by NaHCO3 solution. Mn(III) related to surface lattice oxygen species was responsible for As(III) oxidation. The oxidation and adsorption processes were involved in As(III) removal. The filter media could be successfully applied to simultaneous removal of ammonium, manganese, iron, and arsenic. Abstract : As(III) removal pathway by iron–manganese oxides filter media.